Variation, Modification and Engineering of Lipid A in Endotoxin of Gram-Negative Bacteria - Kawahara, Kazuyoshi (Int J Mol Sci, 2021)
Lipid A of Gram-negative bacteria is known to represent a central role for the immunological activity of endotoxin. Chemical structure and biosynthetic pathways as well as specific receptors on phagocytic cells had been clarified by the beginning of the 21st century. Although the lipid A of enterobacteria including Escherichia coli share a common structure, other Gram-negative bacteria belonging to various classes of the phylum Proteobacteria and other taxonomical groups show wide variety of lipid A structure with relatively decreased endotoxic activity compared to that of E. coli. The structural diversity is produced from the difference of chain length of 3-hydroxy fatty acids and non-hydroxy fatty acids linked to their hydroxyl groups. In some bacteria, glucosamine in the backbone is substituted by another amino sugar, or phosphate groups bound to the backbone are modified. The variation of structure is also introduced by the enzymes that can modify electrostatic charges or acylation profiles of lipid A during or after its synthesis. Furthermore, lipid A structure can be artificially modified or engineered by the disruption and introduction of biosynthetic genes especially those of acyltransferases. These technologies may produce novel vaccine adjuvants or antagonistic drugs derived from endotoxin in the future.